Families, Schools and the Image Communication in the Education Market - Faria Sousa, Susana (International Journal about Parents in Education, 2023)
In this paper we intend to discuss the growing importance of communication as a tool for strategic management of educational institutions, including the communication between schools and parents. Claiming transformational leadership and effective communication system as essential to the success of educational institutions, management turns image communication into a key task, alongside the traditional management of human, financial and resources assets. In Portugal, this task seems hesitantly assumed by the school administration, but in other countries it is already the subject of an advanced theoretical approach. Actually, if many of the factors that influence the recruitment of students are outside the control of schools, the way schools are perceived by families is something that can be managed by them. Collected as part of a doctoral research project, the empirical data supporting this article are the result of observation of everyday life of a group of schools and from the testimonies collected over three years in that setting. In Portugal, it seems to point to the centrality of communication processes in the transformation induced by the new public management on behalf of a ‘quality school’, regardless its exact meaning to the different social actors, including students and their families.